2018
DOI: 10.1124/dmd.118.081935
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between In Vivo CYP3A4 Activity, CYP3A5 Genotype, and Systemic Tacrolimus Metabolite/Parent Drug Ratio in Renal Transplant Recipients and Healthy Volunteers

Abstract: CYP3A5 genotype is a major determinant of tacrolimus clearance, and has been shown to affect systemic tacrolimus metabolite/parent ratios in healthy volunteers, which may have implications for efficacy and toxicity. In a cohort of 50 renal transplant recipients who underwent quantification of CYP3A4 activity using the oral midazolam drug probe, we confirmed that CYP3A5 genotype is the single most important determinant of tacrolimus metabolite/parent ratio [CYP3A5 expressors displayed 2.7- and 2-fold higher rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
(22 reference statements)
3
7
0
Order By: Relevance
“…Our previous data on the metabolism of tacrolimus in ciPTC confirmed a substantially higher rate of tacrolimus metabolism in *1 allele carriers, in line with findings in human liver microsome [40] and clinical data [19,37,41]. In this study, ciPTC with this genetic background also demonstrated a higher absolute and relative propensity for the formation of the M1 metabolite, which was most pronounced in cells with the additional TT genotype.…”
Section: Discussionsupporting
confidence: 89%
“…Our previous data on the metabolism of tacrolimus in ciPTC confirmed a substantially higher rate of tacrolimus metabolism in *1 allele carriers, in line with findings in human liver microsome [40] and clinical data [19,37,41]. In this study, ciPTC with this genetic background also demonstrated a higher absolute and relative propensity for the formation of the M1 metabolite, which was most pronounced in cells with the additional TT genotype.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, we can only hypothesize that, after conversion to LCPT, lower C 2 was a more relevant factor to the improvement of renal function than trough level reduction. Further investigations should also include data on the concentrations of different Tac metabolites, which could be responsible for adverse effects, such as CNIT, infections and myelotoxicity [38,39]. Furthermore, given the retrospective design of this study, the study beginning in the control group had a wide range from March 2017 until August 2018 and the time period from LTx to the beginning of the study was significantly increased compared with that in the intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus is metabolized by CYP3A4 and CYP3A5 and is a substrate of the drug transporter P‐glycoprotein . Patients carrying at least one functional CYP3A5 allele (CYP3A5*1) require approximately twofold higher oral tacrolimus doses than patients homozygous for CYP3A5*3 and appear to be less susceptible to drug–drug interactions with azole antimycotics, which may be explained by stronger inhibition of CYP3A4 than CYP3A5 by azoles . High expression of intestinal ABCB1 messengerRNA (mRNA) (which is translated into P‐glycoprotein) was related to higher dose requirements, but several common ABCB1 polymorphisms were not related to tacrolimus pharmacokinetics, suggesting that P‐glycoprotein is of lesser importance in oral tacrolimus pharmacokinetics.…”
mentioning
confidence: 99%